A Feasibility Study and Design of Biogas Plant via Improvement of Waste Management and Treatment in Ateneo de Manila University - Granada, S (Archīum Ateneo, 2016)
This paper reports the results of feasibility studies on energy production by utilizing the waste produced by Ateneo de Manila University. This approach is environment friendly to reduce CO2 emissions as well as an interesting support to the use local resources as well as reduce landfill disposal. Biogas, as renewable energy form, can properly substitute conventional sources of energy (fossil fuels, oil, etc.) which are causing ecological problems in the fast increasing of CO2 emissions in the atmosphere. The biogas consists essentially of methane (CH4, 50 ÷ 75% by volume), carbon dioxide (CO2, 25 ÷ 45%) and water vapor (H2O, 2 ÷ 7%), as well as other gases in smaller concentrations, including hydrogen sulfide (H2S). The heating value of the biogas is a function of its content in CH4. On average the Net Heating Value can be considered equal to 20,000 ÷ 24,000 kJ/Nm3. The organic component of Municipal Solid Waste (MSW) can be treated anaerobically to produce methane.